Optimizing Learning Evaluation for Students with Special Needs in Elementary Schools - Laili, Faiqoh; Sahlan, Moh.; Saihan, Moh. (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
This study aims to analyze the effectiveness of the Al-Qur'an Hadith learning evaluation method for students with disabilities in inclusive schools, focusing on MI Al-Ikhlas Bagorejo Srono Banyuwangi. Learning evaluation is an activity that teachers must carry out to determine the extent to which learning has succeeded in achieving the desired goals, especially for students with disabilities. This study uses a qualitative approach with a case study type, combining observation, interview, and test techniques. Data validity is tested through triangulation of sources, methods, and time. The study's findings indicate that MI Al-Ikhlas has attempted to adapt to the needs of students with disabilities but still needs improvements in evaluation to meet individual needs. More personalized evaluation methods and more advanced educational technology are key, as is improving teacher training to recognize the variety of educational needs. With these improvements, MI Al-Ikhlas can improve evaluation fairness and support all students' maximum potential in a supportive environment. This study contributes to the development of more personalized evaluation methods for students with disabilities and the integration of educational technology. This supports improving teacher training to create a more inclusive educational environment.